On Pristolepis marginatus, Jerd . (Annals and Magazine of Natural History, 1865)
Objective Accurate transfer of implant positions is critical for achieving passive fit in complete-arch implant-supported prostheses. This clinical case report describes the comparison of eight implant-position acquisition workflows and their influence on the clinical seating of mandibular complete-arch frameworks. The Clinical Seating Score (CSS) was used to assess clinical seating and was compared with three-dimensional deviations. Methods A patient receiving mandibular All-on-4 rehabilitation was treated with four implants placed using dynamic navigation. After a 3-month healing period, implant positions were recorded using eight workflows: conventional open-tray impression, intraoral scanning with conventional PEEK, reduced-height titanium, horizontal-arm, centrally oriented, and reverse scan bodies, intraoral photogrammetry, and extraoral photogrammetry. Eight titanium frameworks were fabricated using standardized CAD/CAM procedures and evaluated intraorally by a single experienced clinician using the CSS (0-6), which assessed framework rocking, screw-tightening tension, and a modified Sheffield test. A Clinical Acceptability Bonus (+1) was assigned when predefined clinical deliverability criteria were met. The framework with the highest CSS was used as the reference for three-dimensional deviation analysis. Results Intraoral photogrammetry produced the highest CSS (6 + 1) and was used as the reference framework. Centrally oriented scan regions and extraoral photogrammetry also produced clinically acceptable seating. Conventional impressions and workflows using conventional PEEK, horizontal-arm, or reverse scan bodies showed greater variability in clinical seating. Deviations of approximately 50-60 μm were generally associated with clinically acceptable seating, whereas discrepancies exceeding approximately 70-80 μm were associated with lower CSS values. These observations suggest that the clinical effect of implant-position discrepancies may vary according to their spatial direction. Conclusions Within the limitations of this single clinical case, the CSS provided a structured approach for assessing the clinical seating of complete-arch implant frameworks. Intraoral photogrammetry demonstrated the most favorable clinical seating, while other workflows showed variable outcomes. The proposed CSS and observed deviation ranges should be considered exploratory and require validation in larger clinical studies. Clinical significance The CSS may potentially provide a simple and standardized chairside method for evaluating the passive seating of complete-arch implant frameworks. This approach may help clinicians identify clinically relevant misfits before delivery of the definitive prosthesis and support more predictable decision-making during framework verification.